A Supply chain management study on Sucere-Twin Oaks Food Corporation - Braga, Virginia Gloria; Tamayo, Teresa Paulette; Segovia, Cesar (Diliman, Quezon City College of Engineering, 2001)
This is a Supply Chain Management study on Sucre-Twin Oaks Foods Corporation. Sucere-Twin Oaks is a leading manufacturer of chocolate and confectioneries for both the consumer and the institutional market. Through thorough documentation of its supply chain, analysis has shown problem areas in the Purchasing, Warehousing and Customer Service Functions. Inadequate forecasting methods have led to raw material shortages and have affected the efficiency in the manufacturing aspect of the supply chain. These shortages have also led to a number of unserved and cancelled orders, which translate to opportunity cost for the company. Using past data for demand, the exponential smoothing method (α = .6) was found to be the most accurate method. In the warehousing component of the supply chain, it was found that improvements could be made in the current stock locater system. In line with this, a set of guidelines are provided in implementing a stock locator system which follows a semi-flexible layout based on the usage rates of the raw materials. The system also uses manual locator cards, which will aid the warehouse personnel in a more efficient way of loading their stock units. It can be determined from the analysis of the Research and Development and Quality Control Department that the customer service function of Twin Oaks/Sucere has a lot of room for improvement. The basic areas wherein progress can be made are (1) the improvement of the feedback mechanism through which customers can communicate, and 92) the use of methods and techniques through which the customer service function can be evaluated. Because of still competition especially from the foreign products, which can boast of a more familiar brand name, Sucere-Twin Oaks is concerned in keeping in touch with their customer base so as to improve both their product and service to their customers. The company already established standard operating procedures regarding the handling of customer complaints. This can be further improved by (1) providing a standard form through which problems can be addressed, and (2) providing a vehicle through which feedback, both critical and non-critical, can be gleaned from clients. It is recommended that customer complaints should be reported in standardized forms so as to easily generate reports and statistics regarding the complaints. The second recommendation is to regularly provide survey forms to institutional customers as a vehicle for feedback
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: Sucere-Twin Oaks Foods Corporation; Chocolate industry; Production management; Industrial procurement; Materials management; System design